Sensitivity-Encoded Diffusion Tensor MR Imaging of the Cervical Cord - Cercignani, Mara (AJNR Am J Neuroradiol, 2003)
Summary: The aim of this study was to apply sensitivity-encoding (SENSE) echo-planar imaging (EPI) to diffusion tensor MR imaging of the cervical cord, an anatomic region where MR imaging is particularly challenging. This technique was implemented with a SENSE reduction factor of 2 and used for imaging a water phantom and five healthy volunteers. Off-resonance artifacts were notably reduced compared with those of full-FOV EPI sequences. This approach to diffusion tensor MR imaging of the cervical cord is promising for future, more extensive clinical applications.